THE EFFECT OF PERSONALITY, WORK PROCEDURE, AND ORGANIZATION CLIMATE TOWARD THE LEADER EFFECTIVENESS OF SENIOR HIGH SCHOOL PRINCIPALS IN DKI JAKARTA PROVINCE - Irmaini Irmaini; Mukhneri Mukhtar; Eliana Sari (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objective of this research is to study the effect of the personality, work procedure, and organization climate towards the leader effectiveness of senior high school principals in DKI Jakarta Province. This research used quantitative approach through survey. The research involved 91 principals as sample by random sampling. The research was conducted on leader effectiveness of principals involving 91 principals as the sample whom had been selected from the target population as many as 117 principals by using quantitative approach with path analysis method. The data were obtained by distributing questionnaire and analyzed by using path analysis. The result of the research can be concluded: (1) the personality, work procedure, and organization climate had a positive direct effect on leader effectiveness; (2) the personality and work procedure had a positive direct effect on organization climate. Thus, the stakeholders on senior high school of DKI Jakarta Province need to take concrete steps to ensure that in a senior high school environment with a personality and work procedure that guarantee the existence of the senior high school in the future. The implication and limitation of the study are discussed along with the suggestion for further research. Keywords: Personality, Work Procedure, Organization Climate, And Leader Effectiveness